(untitled) (Al-Academy, 2017)
T.V photo in modern shows has emerged with special characteristics and signs that have developed in cope with the development of medium and technique. This leads to adding a variety of aesthetic dimensions which are capable of attracting audience because of its communicative elements that have an important role in increasing of T.V show Watching. As a result, the research is limited to methodological Framework as the problem. The problem of the research deals with emerging the aesthetic dimensions of T.V photo. The major question is (what are the aesthetic and communicative dimension of T.V Photo?). The research aims at finding out the aesthetic dimensions of T.V photo in modern artworks. The significance of the research on the presented problem, because the limitation of the impressions of aesthetic of photo according to its communicative side may form a great importance for both students and researchers. In addition to, Iraqi media communities. Because of diverse work in T.V shows and satellite channels, the researcher has found it difficult to restrict the limits of the research. Thus, a selected sample has been chosen. This sample has been represented in the show of (al-mataha) produced by MBC group. The theoretical framework has divided into two sections. the first section (the communicative features of T.V photo). The second sections deals with (the attraction media of T.V photo ). The researcher has different to pies that have been adopted as an analysis tools of the fourth chapter. The researcher has drawn many conclusions like: 3d techniques have communicative effective role across the aesthetic dimension that it adds to T.V photo. Recommendations and suggestions have been presented